2013
DOI: 10.15193/zntj/2013/91/151-164
|View full text |Cite
|
Sign up to set email alerts
|

MICROENCAPSULATION OF Α-Tocopherol INSIDE SACCHAROMYCES CEREVISIAE YEAST CELLS

Abstract: MIKROKAPSUŁKOWANIE α-TOKOFEROLU WEWNĄTRZ KOMÓREK DROŻDŻY SACCHAROMYCES CEREVISIAES t r e s z c z e n i e W pracy oceniono przydatność drożdży Saccharomyces cerevisiae jako naturalnego materiału nośni-kowego w procesie mikrokapsułkowania witaminy E oraz ustalono optymalne warunku tego procesu.Witaminę E, w formie DL-α-tokoferolu, mieszano z porcją drożdży oraz wodnym roztworem alkoholu etylowego i inkubowano przez 48 h w temperaturze od 25 do 55 °C. Przy użyciu metody płaszczyzny odpowiedzi (RSM) oceniono wpływ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…A large variety of hydrophobic compounds have been encapsulated in yeast, mostly in S. cerevisiae and predominantly for food applications. Intact cells have been employed for the encapsulation of terpenes (limonene, linalool and carvone [ 31 ]), perfumes [ 44 ], cryoprotectants [ 85 ], water-insoluble drugs (Itraconazole fenofibrate [ 86 ] and econazole nitrate [ 67 ]), orange peel essential oil [ 42 , 87 ], and antioxidants (α-tocopherol [ 88 ]). Although the process works in the absence of additional treatments, several comparative studies have demonstrated that encapsulation in intact cells is less efficient than that in plasmolyzed (see next section) ones; this has been shown with a variety of actives (e.g., purslane seed oil [ 89 ], cholecalciferol (vitamin D3) [ 90 ], barberine [ 91 ] and curcumin [ 92 , 93 ]).…”
Section: Ybmcs–one Name Different Materialsmentioning
confidence: 99%
“…A large variety of hydrophobic compounds have been encapsulated in yeast, mostly in S. cerevisiae and predominantly for food applications. Intact cells have been employed for the encapsulation of terpenes (limonene, linalool and carvone [ 31 ]), perfumes [ 44 ], cryoprotectants [ 85 ], water-insoluble drugs (Itraconazole fenofibrate [ 86 ] and econazole nitrate [ 67 ]), orange peel essential oil [ 42 , 87 ], and antioxidants (α-tocopherol [ 88 ]). Although the process works in the absence of additional treatments, several comparative studies have demonstrated that encapsulation in intact cells is less efficient than that in plasmolyzed (see next section) ones; this has been shown with a variety of actives (e.g., purslane seed oil [ 89 ], cholecalciferol (vitamin D3) [ 90 ], barberine [ 91 ] and curcumin [ 92 , 93 ]).…”
Section: Ybmcs–one Name Different Materialsmentioning
confidence: 99%
“…The yeast microcapsules containing fish oil were prepared using modified procedure proposed by Bishop et al (1998). One of the differences from the original procedure was the addition of ethyl alcohol to the emulsion which was supposed to facilitate the diffusion of oil into the cells (Czerniak and Jankowski, 2013). Fish oil (20 g) was mixed with deionized water (80 g) containing soy lecithin as an emulsifier.…”
Section: Enzymatic Hydrolysis With B-glucanasementioning
confidence: 99%